A multi-faceted financial crisis - Roncaglia, Alessandro (PSL Quarterly Review, 2011)
Nearly three years after the deluge, the financial crisis is in many different ways still with us: from its consequences on the real economy, to the clearly perceived risk of new catastrophes, from its role in engendering social malaise and political events such as the revolts in Arab countries, to its impact on the theoretical and policy debate in economics. With the present issue, once again our journal focuses its attention on the crisis – the theoretical and applied debate on the factors leading to it and its policy implications – in an attempt to contribute to our understanding of the main economic event of the past decade, still in many ways unfolding. JEL Codes: E11, G01, B50, H12